On contraction and compensatory lengthening in Baltic ē-stems - Hill, Eugen (Baltistica, 2024)
This paper deals with those verbal and nominal ē-stems of Baltic which exhibit a secondary lengthening of short vowels in the root and/or a secondary metatony in acute long vowels or diphthongs. These are a particular class of ē-preterits as well as feminine abstract nouns based on adjectives and verbs. In both cases, the stem formative is traditionally explained as having arisen from a more ancient post-consonantal *-ā. This paper argues that both categories can be explained by assuming a change of early-Proto-Baltic post-consonantal * into *i when followed by a long vowel or diphthong.